2022
DOI: 10.25128/2520-6230.22.2.10
|View full text |Cite
|
Sign up to set email alerts
|

The development of inclusive competence in the system of postgraduate education: theoretical, methodological and practical aspects

Abstract: The relevance of the study is determined by the need to develop teachers’ inclusive competence in the system of postgraduate education. The article analyzes inclusive competence as a component of the professionalism of a modern teacher. The main attention is focused on the analysis of the peculiarities of the organization of the educational process at the Postgraduate Education Centre in the scope of formation of teachers’ inclusive competence. The content of educational programs has been revealed. The effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Основним напрямом удосконалення рівня професійної компетентності педагога залишається професійне самовдосконалення через цілеспрямовану самоосвітню діяльність [3].…”
Section: п самоосвітня діяльність педагога як чинник змін освітнього ...unclassified
“…Основним напрямом удосконалення рівня професійної компетентності педагога залишається професійне самовдосконалення через цілеспрямовану самоосвітню діяльність [3].…”
Section: п самоосвітня діяльність педагога як чинник змін освітнього ...unclassified
“…The educational qualification of the participants who developed their ideas with akmeolojik research is positively shown in Table 7. Kalaur, Slozanska, and Honcharuk (2022) in the year of the work they have done according to the need to develop competencies in the system of postgraduate training sought to determine the container, and as a result, the study of teachers in the formation of the adequacy of the container under the organisation of the educational process and the features of graduate education in the centre of the container also focused on the analysis of the effectiveness of the implementation of the competencies that are useful in the formation of akmeolojik observed that the approach achieves the result. In this context, the results of the research using this value, when combined with akmeolojik of time during the day and up to 5 hours of training, it is seen that the above conclusion is reached, and professional competence and inclusive akmeolojik education with training can be argued based on the related studies.…”
Section: Acmeological Competence Opinions Of the Study Participant Gr...mentioning
confidence: 99%
“…As a result of these efforts, inclusive education creates conditions for equal access to education and the inclusion of all categories of students, especially those with physical disabilities (Kalaur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%